Epidemic features and clinical analysis of pediatric Mycoplasma pneumoniae respiratory infection before, during, and after COVID-19 pandemic: a 7-year study in southern China - Chen, Aiping; He, Qiaoqiao; Xiao, Zhigang; Wu, Yiqiu; Zhong, Huan; Lu, Gen; Fan, Huifeng (Translational Pediatrics, 2026)
In the period spanning 2023 to 2024, there was a global resurgence of Mycoplasma pneumoniae (M. pneumoniae) infections following the coronavirus disease 2019 (COVID-19) pandemic. This 7-year retrospective study investigated the epidemic features and clinical severity of pediatric M. pneumoniae respiratory infection in southern China across the pre-, during, and post-COVID-19 periods.